CD80 Antibody and MTX Co-Engineered Extracellular Vesicles Targets CD80+ Macrophages to Suppress Inflammation and Alleviate Chronic Inflammatory Diseases - Yang J; Zhang H; Wang W; Yin Q; He X; Tao D; Wang H; Liu W; Wang Y; Dong Z; Chen X; Li B (International Journal of Nanomedicine, 2025)
Jianhua Yang,1,* Handan Zhang,2,* Wenzhe Wang,1,* Qiqi Yin,2,* Xiaoning He,1 Dihao Tao,1 Hanzhe Wang,1 Wenhao Liu,1 Yiming Wang,1 Zhiwei Dong,3 Xin Chen,2 Bei Li1 1State Key Laboratory of Oral & Maxillofacial Reconstruction and Regeneration, National Clinical Research Center for Oral Diseases, Shaanxi International Joint Research Center for Oral Diseases, Center for Tissue Engineering, School of Stomatology, The Fourth Military Medical University, Xi’an, People’s Republic of China; 2Department of Chemical Engineering, Shaanxi Key Laboratory of Energy Chemical Process Intensification, Institute of Polymer Science in Chemical Engineering, School of Chemical Engineering and Technology, Xi’an Jiaotong University, Xi’an, 710049, People’s Republic of China; 3Department of Oral and Maxillofacial Surgery, College of Stomatology, Xi’an Jiaotong University, Xi’an, People’s Republic of China*These authors contributed equally to this workCorrespondence: Bei Li, State Key Laboratory of Oral & Maxillofacial Reconstruction and Regeneration, School of Stomatology, The Fourth Military Medical University, Xi’an, Shaanxi, 710032, People’s Republic of China, Email libei2021@fmmu.edu.cn Xin Chen, Institute of Polymer Science in Chemical Engineering, School of Chemical Engineering and Technology, Xi’an Jiao Tong University, Xi’an, Shaanxi, 710049, People’s Republic of China, Email chenx2015@xjtu.edu.cnIntroduction: Aberrant interaction between innate immune and adaptive immune cells can disrupt tissue homeostasis, consequently triggering chronic inflammatory diseases such as rheumatoid arthritis (RA) and periodontitis (PD). Pro-inflammatory macrophages serve as critical mediators in the early immune response, constituting a major population of CD80+ cells, while anti-inflammatory macrophages modulating inflammatory processes through the secretion of transforming growth factor-beta (TGF-β). This cytokine facilitates the differentiation of peripheral regulatory T cells (Tregs) and contributes to the establishment of immune tolerance. However, there are no definitive therapies to reshape the tissue homeostasis between innate immune and adaptive immune cells.Methods: (1) anti-CD80-MTX-EVs was obtained by gradient centrifugation, which were characterized by TEM and DLS, and the associated membrane proteins were identified by Western Blot. (2) The mouse bone marrow-derived macrophages were co-cultured separately with EVs, anti-CD80-EVs, and anti-CD80-MTX-EVs in vitro, and the expression of CD80 on the macrophages surface as well as the proportion of Treg cell generation were detected. (3) EVs, anti-CD80-EVs and anti-CD80-MTX-EVs were injected into mice models of arthritis and periodontitis for treatment, the therapeutic effect was evaluated by the expressions of related cytokines, staining of HE, the proportion of CD80+ macrophages and the phenotypic differentiation of T cells in the tissues.Results: We successfully constructed engineered EVs (anti-CD80-MTX-EVs) targeting inflammatory macrophages for intracellular MTX delivering, which inducing the anti-inflammatory transformation while upregulating the expression of TGF-β of macrophages. Furthermore, our findings demonstrate that anti-CD80-MTX-EVs effectively reduce CD80+ macrophage levels, promote Treg cell generation, and inhibit Th1 cell production in vivo.Conclusion: In this study, the anti-CD80-MTX-Evs demonstrated significant therapeutic effects in both rheumatoid arthritis and periodontitis models through a triple mechanism: reducing CD80+ macrophage population, enhancing Treg cell differentiation, and suppressing Th1 cell development. Overall, this study presents an innovative strategy for resolving inflammation within chronic inflammatory diseases.Keywords: anti-CD80-MTX-EVs, macrophages, rheumatoid arthritis, periodontitis, immune tolerance, Treg cells